A palavra do outro ouvida e respondida: uma compreensão enunciativa sobre a atividade de recontar histórias nas séries iniciais - Cardili, Wuendy Fernanda (2014)
On the assumption that a text is the guiding object for both teaching and learning, according to words by Geraldi (2003; 2010), the aim of this study is the analysis of written stories retold by students who are in process to become literate and focuses on how a otherness word becomes their own word in written production. Based on enunciative studies of language and on Bakhtin, it is assumed the idea of language as an interactive process and the constitution of the subject. The literacy is comprehended as a discursive process. Thus, the written language acquisition is considered from the relationship between subjects with, about and of the language. The corpus which permitted such analysis is formed by twenty four texts of middle school students from 2nd grade, written in 2010, based on the story Menina bonita do laço de fita by Ana Maria Machado. The genre retelling constitutes of an activity of retelling and happens to be from the perspective of counter-word of somebody else s discourse, in which the students written productions are the answer to somebody else s discourse.The paradigm of evidence, developed by Ginzburg (1986), is the methodological approach used to analyze the written productions and allows the comprehension of the singularity evidences related to written process. The association between the paradigm of evidence and the studies related to written acquisition allows the comprehension of the subject s dialogical relation processes and language. It was intended to develop a reflexive look at texts from the appropriation of the Otherness word. When in contact with other words, the subjects create their own words and by doing so build up meanings for the story. This creation process about language proves that retelling is not a reproduction, but the production of the new. The author s appropriation of words is assimilated to the subjects own words, in the new retold story, whose meeting the word, results in the production of a new text, a new, single and not-repeated enounced in enunciation chain. The retelling presupposes evaluation, comprehension and active and responsive activity in relation to somebody else s discourse. Thus, the dialogic relationship between some enounced, achieved through the activity of retelling reveals itself as an important strategy to produce meanings, in which the retelling allows a (re) signification of written work in school settings.